Perception technology of virtual threat for large enterprise's information security construction - Ying XU; Zhao WU; Zhiqi LI (Dianxin kexue)
Facing with the rapid develop ment of the progress of the information construction, how to effectively achieve the risk prevention and control, in order to build the advanced, practical, safe and reliable information security system, is a severe test to every large enterprise. By analyzing the main characteristics of various security risks and the information security protection, which are faced by large enterprises in the information construction, the practical ideas for the construction of information security system was put forward. Furthermore, the threat that faced by the large enterprise's virtual environment of information security construction was analyzed, a virtual threat perception system was destgned, which consists of threat intelligence platform, the local detection system and data analysis platform.